Effect of aspect ratio on frequency and power generation of a free-piston linear generator - Zainal A., E.Z. (Elsevier Ltd, 2021)
The thermal efficiency (40â50) of free-piston linear generator (FPLG) engines is widely known to be higher than the conventional reciprocating engine (CRE) (30â40). Future technology to optimise FPLG engine combustion necessitates the identification of a stroke to bore ratio (Aspect Ratio, AR). This paper presents a report on the effects of different aspect ratios (1, 1.5, and 2) on the FPLG operating frequency and power output. The development of an experimental test rig was through the utilisation of the FPLG principle of a dual-piston (bounce and combustion chamber) air-driven system. The mechanical function of the FPLG is converted into electric power through the linear generator. The piston velocity, power output (Prms), operating frequency, as well as system energy density and conversion efficiency are discussed in the paper. The FPLG operation using long-stroke (AR2) shows obvious advantages in the peak velocity and Prms; however, the operating frequency is higher in the short stroke, although the in-cylinder pressure, compression ratio, and piston velocity are slightly lower. The calculated energy density indicates the medium stroke (AR1.5) is the optimum in the operating frequency and Prms for overall FPLG operation; besides, it works perfectly in a lean condition. The shortest stroke has better combustion efficiency (38.5) at the stoichiometric condition; however, this percentage significantly increased in a lean condition (ER = 0.4) for AR1.5 and AR2 to 55.67 and 62.39, respectively, with an increment of 49.3 and 46.6. The system conversion efficiency decreases with the increase of the aspect ratio. Â© 2021 Elsevier Ltd